IDENTIFICATION OF ASSET MANAGEMENT AND FINANCIAL PERFORMANCE ON MARKET VALUE OF PROPERTY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Clara Neltje Meini Rotinsulu; Jacomina Vonny Litamahuputty; Agnes Soukotta; PA. Andiena Nindya Putri (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to analyze how much influence asset management and financial performance have on the market value of property companies listed on the Indonesia Stock Exchange. The design of this study uses secondary data, with a purposive sampling technique, namely property sector companies, with the property and real estate and building construction sub-sectors, which are listed on the Indonesia Stock Exchange, as many as 67 observations. The operational variable of this research is Asset Management measured based on Fixed Asset Turnover (FAT) and Inventory Turnover (IT); and Financial Performance is measured based on Return On Assets (ROA) and Return on Equity (ROE) to Market Value which is measured based on the Closing Share Price (HSP). The analysis of this study uses the classical assumption test and hypothesis testing.